Il mito dell’appartenenza. Politeia greca e civitas romana a confronto - Errede, Giovanna (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2019)
This essay aims to investigate the origin of the concepts of citizenship and democracy through a reflection on the condition of the citizen in the poleis of ancient Greece – with a particular focus on legal systems in Sparta and Athens – and within the Roman Republic and Empire. Beyond the traditional (and simplistic) distinction between “Roman generosity” and “Greek avarice”, the landscape of ancient citizenship turns out to be very diverse and complex, regulated by the criteria for selecting the community of participants to political life; these criteria not only distinguish the Roman world from the Greek one, but also the Spartan polites from the Athenian one. The present reflection, which is not limited to a mere description of ancient legal systems, means to emphasise how much the concept of citizenship, since the beginnings of Western culture, was closely linked to the dichotomy inclusion/exclusion, to a strongly and meticulously hierarchized politics, to the interpretation of the border as entry threshold for the foreigner, but also as an instrument of expansion and conquest. Citizenship; Democracy; Inclusion; Polis; Rome.